CHATIB SUTAN SEBAGAI TOKOH PEJUANG PERINTIS KEMERDEKAAN DI INDRAGIRI 1940-1974 - Satriadi Satriadi; Isjoni Isjoni; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak: Chatib Sutan is a fighter figure Indonesian republic independence’s pioneer who was from Cerenti, the regency of Kuantan Singingi. Someone used to be said an independence’s pioneer was those who struggled to bring Indonesian nation to the acme of Independence destination and also those who were recognized and legitimaked by a social ministry decree of Indonesian republic. The objective of this research is to find the biography of Chatib Sutan from his childhood, education, household life to his struggles in doing pioneering work in Indonesian the data were gained from books telling stories of Chatib Sutan’s struggles and bg doing a feew interviews with reliable people on the remarks they gave. The location of the research was in the subdistrick of Cerenti, the regency of Kuantan Singingi. This research was conducted starting from being issued a research letter until this thesis finished. The data collection technique used in this research were interview, documentation, and libary observation. The research finding showed that Chatin Sutan is a fighter figure of Indonesian republic Independence’s pioner based on the social ministry decree no. Pol 421/70/PK on 18th of February 1971. The struggles done by him were in the period of Netherlands and Japan’s colonialism as well as military aggresion of the Netherlands.Key Words : Chatib Sutan fighter indenpendence pioner